Faktor yang mempengaruhi kejadian asfiksia neonatorum di RSUD Wangaya Kota Denpasar - Bella Kurnia; I Wayan Bikin Suryawan; A.A. Made Sucipta (DiscoverSys Inc., 2020)
Background: Birth asphyxia is a serious clinical problem worldwide. There are many reasons a baby may not be able to take in enough oxygen before, during, or just after birth. Birth asphyxia is the inabiity of neonates to start breathing spontaniously right after birth.Objective: This study was designed to assess the risk factors of birth asphyxia in neonates in Wangaya General Hospital.Methods: It is a case control study. The data of the newborn and mother was retrospectively collected from medical record in Wangaya Regional General Hospital between November 2018 to March 2019. It uses consecutive sampling. Bivariate analysis using chi square and multivariate analysis using logistic regresssion.Results: Bivariate analysis of risk factors of birth asphyxia that are studied are: low birth weight p value 0.000 (OR: 30.118); Number of birth p value 0,013 (OR 4,025); Prematurity p value 0.001 (OR 18.286); PROM p value 0.751 (OR 1.508); preeclampsia p value 1.000 (OR 0.804); and Cesarean Section p value 0.218 (OR 0.479). From multivariate analysis, the result was low birth weight p value 0.020; number of birth p value 0.003; prematurity p value 0.766; caesarean section p value 0,028.Conclusion: Risk factor of birth asphyxia in Wangaya General Hospital are low birth weight; number of birth (Primipara); and caesarean section.Â Latar Belakang: Asfiksia neonatorum adalah suatu kondisi yang serius di seluruh dunia. Ada beberapa penyebab dimana bayi tidak bisa mendapatkan oksigen yang cukup sebelum, selama, atau setelah lahir. Asfiksia neonatorum adalah keadaan dimana neonatus tidak dapat memulai bernafas dengan spontan segera setelah lahr.Penelitian ini dilakukan untuk melihat faktor resiko terjadinya asfiksia neonatorum pada neonatus di RSUD Wangaya.Metode: Penelitian ini adalah penelitian case control. Data neonatus dan data ibu diambil dari data rekam medis di RSUD Wangaya sejak November 2018 hingga Maret 2019. Studi ini menggunakan consecutive sampling. Analisa bivariat menggunakan chi square dan analisa multivariat menggunakan regressi logistik.Hasil: Hasil dari analisa bivariat adalah: BBLR p value 0,000 (OR: 30.118); Paritas p value 0,013 (OR 4,025); Prematuritas p value 0.001 (OR 18.286); KPD p value 0.751 (OR 1.508); Preeklampsia p value 1.000 (OR 0.804); and Bedah Caesar p value 0.218 (OR 0.479). Dari analisa multivariat, hasilnya adalah BBLR p value 0.020; Paritas p value 0.003; prematuritas p value 0.766; bedah sesar p value 0,028. Simpulan: Fakor resiko terjadinya asfiksia neonatorum di RSUD Wangaya adalah BBLR; Paritas (Primipara); and bedah sesar.